Adoption of Agroforestry Practices: Chi2 Function Approach in Determining Influence of Individual and Social Factors on Farmers’ Decision to Adopt or not to Adopt Agroforestry - Himshikha; Singh, Charan (Indian Forester, 2018)
A wide range of factors influence farmers decision to adopt agroforestry practice, and it ranges from household to social and economic consideration. This research work, therefore, led to investigating the influence of some individual and social factors on agroforestry adoption by the farmers in Haridwar, India. Besides these factors, some other factors were also studied to examine their association with adoption. Using random sampling and field survey techniques, data was collected from a total of 426 farmers (365 agroforestry and 61 non agroforestry farmers). Total 17 individual and social attributes were analyzed using Chi2 analysis (test of independence at Ã¡=0.05 level of significance) approach. These factors were age, gender, marital status, family size, level of education, land holding or farm size, approach to forest to meet their livelihood requirements, knowledge about related schemes and technologies, training programmes, total farming experience, house type, reason behind farming practices, perception about farming output, resources availability. Results have shown that a number of factors such as age, experience, landholding etc are statistically significant and hence influence adoption of agroforestry. While other factors such as gender, education, decision making etc are not statistically significant and hence do not influence adoption of agroforestry by the farmers.